جماليات التبئير في رواية " التّبر" لإبراهيم الكوني - حفري، فاطمة الزهراء; حبى، خولة; موني، مفيدة (University of Eloued جامعة الوادي, 2024)
الملخص: يهدف البحث إلى دراسة التبئير في رواية التّبر لإبراهيم الكوني ، في سياق الكشف والبحث عن مختلف أنواع التبئير الداخلي والخارجي والمعدوم في الرواية التي تمتاز بالخصوصية والمحلية في الرؤى المتخيلة ، بحيث تناولت الفضاء الصحراوي وعلاقة الإنسان بحيوان الجمل ، وقد خلصت الدراسة التطبيقية إلى : ممارسة إبراهيم الكوني فعل التفسير في ثنايا الحكي وهامشه فيظهر الراوي الإخباري التوثيقي في هامش الحكي ليؤرخ لما غمض من أساطير ومعاني فالراوي > الشخصية وأعلم منه وهذا ما يسمى بالرؤية من الخلف فالكوني هو السارد كليّ المعرفة استعمل ضمير الغائب في سرد ما ظهر وما خفي وكل ما تعلق بالرواية من شخصيات وأزمنة وأماكن وأحداث فهو راوي عليم بكل مجريات الرواية وهو ما يسمى بالتبئير المعدوم (الصفر)الذي لم يرد غيره في هذه الرواية . Résumé : فرنسية أو انجلزية The research aims to study preaching in the novel of Gold Dust (Ettiber) by Ibrahim AlKoni in the context of revealing and searching for various types of internal, external and nonexistent preaching in the novel which is characterized by brivacy and locality in the imaginative visions, as it deals with the desert space and the human relationship with the camel. So the applied study has coneluded that: Ibrahim ALkoni practiced the act of interpretation in the folds and whispers of the narrating, so the narrator appears as a documentary reporter in the margins of the narration to chronicle the myths and meanings that have been obscured the narrator is the character and he is more knowledgeable than it. This is what is called seeing from behind. Elkoni is a narrator which used the thirdperson pronoun in narrating what is apparent and what is hidden. He is also the absent person with a complete knowledge about everything related to the novel including characters, times, places, and events, He is a narrator who Knows all the events of the novel. This is called zero evangelism, which he did not change it in this novel.
Keywords: : جماليات التبئير، رواية التبر، تقنيات التبئير focus aesthetics; focus narrative; focus techniques.